Handbook on fact-finding and documentation of human rights violations, based on a workshop ... 1-6 October 1993, Chiangmai, Thailand - Guzman, Manuel; Ignacio, Johannes L.; Ravindran, D.J (Asian Forum for Human Rights and Development (FORUM-ASIA) and Union for Civil Liberty-Thailand, 1994)
The purpose of the handbook is to help human rights organizations in undertaking systematic fact-finding and documentation of human rights violations and thereby strengthening their role in protection of human rights.